Assessing the Effectiveness of Support Strategies in Reducing Professional Burnout Among Clergy Serving in The Presbyterian Church (USA). Issue 3 (1st January 2013) - Francis, Leslie J.; Robbins, Mandy; Wulff, Keith
Abstract The pastoral care and support of the clergy is an issue of growing concern to denominational leaders in the light of reported levels of stress in ministry, sickness, and early retirement. Drawing on the balanced affect model of professional burnout proposed by the Francis Burnout Inventory and the dimensional model of personality proposed by the abbreviated Eysenck Personality Questionnaire Revised, this study assesses the effectiveness of five support strategies operated by The Presbyterian Church (USA) to reduce levels of professional burnout among the clergy: study leave, sabbaticals, ministry mentors, spiritual directors, and minister peer groups. Data provided by a random sample of 744 clergy demonstrated that, after controlling for individual difference in age and personality, none of the five examined strategies served as predictors of lower levels of emotional exhaustion in ministry, but two strategies served as predictors of enhancing satisfaction in ministry, namely having a mentor and taking study leave.